Experimental investigation of impact loading on honeycomb sandwich panels filled with foam. Issue 2 (4th March 2019) - Hassanpour Roudbeneh, Fatemeh; Liaghat, Gholamhossein; Sabouri, Hadi; Hadavinia, Homayoun
ABSTRACT: In this paper, experimental studies of impact loading on honeycomb sandwich panels filled with polymer foam were investigated. The structural elements used in this research were aluminium plate, aluminium 5052 honeycomb structure and three types of polyurethane foam with densities 56.94 (foam1), 108.65 (foam2) and 137.13 (foam3) kg/m 3 . Failure mechanisms and damage modes, ballistic limit velocities, absorbed energies due to penetration, specific perforation energy capacity and some structural responses were analysed. The effect of foam-filling on ballistic impact response in these honeycomb sandwich panels was discussed. Also, it could be found that there was an increase in the dynamic strength of the sandwich structure when the honeycomb core was filled with foam. In addition, the findings demonstrated that the sandwich panels filled with the highest density foam (Type 3) had the highest ballistic limit velocity and specific absorbed energy. The specific energy absorption of this structure was 24% higher than the unfilled one.